Influence of Ocular Residual Astigmatism on the Correction of Myopic Astigmatism by Toric Implantable Collamer Lens: A Comparative Study With Femtosecond Laser Small Incision Lenticule Extraction - Sun, Ling; Zhang, Xiaoyu; Ding, Lan; Shen, Yang; Qian, Yishan; Zhou, Xingtao (Frontiers in Medicine, 2022)
Purpose: To evaluate the influence of the origin of astigmatism on the correction of myopic astigmatism by toric implantable collamer lens (TICL) and compare it with femtosecond laser small incision lenticule extraction (SMILE). Methods: Ocular residual astigmatism (ORA) was determined by vector analysis using manifest refraction and Scheimpflug camera imaging of the anterior cornea. One-to-one matching between the TICL and SMILE groups was performed by preoperative manifest refractive astigmatism (RA) and ORA, tolerating a maximum difference of 0.50D for RA and 0.25D for ORA. Patients of each group were further divided into groups according to ORA (high >1.0 diopter [D]; low ≤1.0 D). Baseline and 12-month postoperative data were analysed. Data are expressed as mean ± standard deviation (SD). A P value less than 0.05 was considered statistically significant. Results: For the TICL group, no significant differences in the postoperative RA, safety index, efficacy index, index of success (IOS), correction index (CI) and angle of error (AOE) were found between high (n=36) and low ORA (n=36) groups (Mann-Whitney U test, P>0.05). For the SMILE group, the postoperative RA (high: -0.67±0.43 D, low: -0.39±0.29 D, Mann-Whitney U test, P=0.003) and IOS (high: 0.50±0.43, low: 0.25±0.23, Mann-Whitney U test, P=0.003) were greater in the high ORA group. When comparing TICL and SMILE groups, the mean postoperative RA (TICL: -0.48±0.29 D, SMILE: -0.67±0.43 D, Mann-Whitney U test, P=0.03) and IOS (TICL: 0.32±0.23, SMILE: 0.50±0.43, Mann-Whitney U test, P=0.03) were significantly higher in the SMILE group when the ORA was >1.0 D. Conclusions: Both TICL and SMILE are effective in correcting myopic astigmatism. ORA has a lesser effect on TICL than on SMILE.